Caracterização geológica-estrutural da região aurífera de Santa Rita (Jeroaquara), norte do Greenstone Belt de Faina (GO) - Martins, José Eduardo da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Faina Greenstone Belt (FGB) is a NW-SE/SW (strike/dip), 50 km length and 6 km outward width structure, located in the Goiás Archean Block, a Granite-Greenstone terrain inserted in the Inner Brasilia Fold Belt, central Brazil. The Goiás Archean Block hosts five Greenstone Belts Terrains (Crixás, Guarinos, Pilar, Serra de Santa Rita and Faina), the first three host proved gold deposits that are currently exploited, whilst Santa Rita and Faina remain under explored. Despite being under surveyed the FGB shows many vestiges of past gold exploitation, such as various shaft works from Brazilian colonial period, such those of Cascavel Project, and more recent activities such as the disabled Sertão Mine. Orinoco Gold is currently the main player in the mineral surveying in the area; this final academic work was developed by the author during a trainee period at the exploration company. The work was a detailed (1:10.000) geological and structural mapping of a 40 km2 area in the north portion of the FGB, westwards of Santa Rita (Jeroaquara) village. The interest in this region goes by the fact that it was registered significant gold, silver, chromium and copper grades by chip sampling and whole rock analysis in this area. Also, the area is just southwards of Eliseu Target (in the same structural trend), where whole rock analysis and drilling core showed important gold occurrences. The work allowed delineating a complex stratigraphic and structural setting for this portion of the FGB. The rocks of the area are structured as four tectonic domains separated by major NW-SE/SW (strike/dipdir), NE vergence thrust faults. In the studied area these faults cause significant tectonic truncations that dictate the outcrop pattern in this part of FGB. Also macroscopic folds mapped in the area, related to various deformational phases, influences in the rocks exposition in the area. The three upper domains coincide...

O Greenstone Belt de Faina (GBF) é uma faixa de atitude NW-SE/SW (direção/rumo do mergulho), de 50 km de comprimento 6 km de largura em sua porção central, inserido no Bloco Arqueano de Goiás, um terreno Granito-Greenstone alojado na porção interna da Faixa Brasília. O Bloco Arqueano de Goiás abriga cinco faixas Greenstone Belt (Crixás, Guarinos, Pilar, Serra de Santa Rita e Faina), os três primeiros hospedam significativos depósitos provados de ouro, que são atualmente explorados, entretanto os Greenstone Belts de Santa Rita e Faina permanecem menos estudados. Apesar de ser menos prospectado, o Greenstone Belt de Faina mostra muitos vestígios de explorações antigas de ouro, tal como os garimpos do período colonial, tal como o Projeto Cascavel, e também evidências de atividades mais recentes, tal como a Mina Sertão, atualmente desativada. A Orinoco Gold é atualmente a principal empresa com atividades exploratórias na área; estre trabalho de conclusão de curso foi desenvolvido pelo autor enquanto esta realizada estágio na referida empresa. O trabalho realizado foi o mapeamento e caracterização geológica-estrutural de uma área de 40km2 na porção norte do GBF, a oeste da localidade de Santa Rita (Jeroaquara). O interesse nesta região se deu, pois foram obtidos teores significativos de ouro, prata, cromo e cobre em amostragem de chip e análise química de rocha total., e também pois se situa imediatamente a sul do Alvo Eliseu, onde foram identificadas importantes ocorrências de ouro através de amostras de chip e de furos de sonda. Este trabalho permitiu delinear o complexo quadro Tectono-estratigráfico desta porção do GBF. As rochas da área estão estruturadas na forma de quatro domínios lito tectônicos separados entre si por falhas de empurrão de primeira ordem, de atitude NW-SE, vergência para NE. Estas falhas de empurrão causam expressivos truncamentos...
Keywords: Geologia estrutural; Mapeamento geologico; Prospecção mineral; Greenstone belts; Ouro - Minas e mineração; Minas e recursos minerais; Geologia estratigráfica; Faina (GO)